Mentor judgements and decision‐making in the assessment of student nurse competence in practice: A mixed‐methods study. (18th December 2017) - Burden, Sarah; Topping, Anne Elizabeth; O'Halloran, Catherine
Abstract: Aim: To investigate how mentors form judgements and reach summative assessment decisions regarding student competence in practice. Background: Competence assessment is a significant component of pre‐registration nursing programmes in the United Kingdom. Concerns exist that assessments are subjective, lack consistency and that mentors fail to judge student performance as unsatisfactory. Design: A two‐stage sequential embedded mixed‐methods design. Data collected 2012–2013. Methods: This study involved a whole student cohort completing a UK undergraduate adult nursing programme ( N = 41). Stage 1: quantitative data on mentor conduct of assessment interviews and the final decision recorded ( N = 330 from 270 mentors) were extracted from student Practice Assessment Documents (PADs). Stage 2: mentor feedback in student PADs was used in Stimulated Recall interviews with a purposive sample of final placement mentors ( N = 17). These were thematically analysed. Findings were integrated to develop a theoretically driven model of mentor decision‐making. Results: Course assessment strategies and documentation had limited effect in framing mentor judgements and decisions. Rather, mentors amassed impressions, moderated by expectations of an "idealized student" by practice area and programme stage that influenced their management and outcome of the assessment process. These impressions were accumulated and combined into judgements that informed the final decision. This process can best be understood and conceptualized through the Brunswik's lens model of social judgement. Conclusion: Mentor decisions were reasoned and there was a shared understanding of judgement criteria and their importance. This impression‐based nature of mentor decision‐making questions the reliability and validity of competency‐based assessments used in nursing pre‐registration programmes.